(untitled) (Indian Journal of Animal Production and Management, 2017)
A field survey was conducted in Jalalpore taluka of Navsari district to ascertain the housing and health care management practices followed by dairy animal owners and data was collected from randomly selected 150 dairy animal owners through personal interview with the help of pre-tested structured schedule. The present study revealed that majority of respondents provided close type (55.33%) and kuchcha type (54.67%) houses. Majority (90%) of respondents kept their animals inside the house both during day and night, 61.33% of animal sheds were nearby to the dwelling of the farmer. About 42% of respondents had pucca floors to their animal houses, 53.33% of respondents used cemented type poles to their animal houses. Majority (71.33%) of respondents provided manger to their animals, only 23.33% of respondents had pucca type of manger and 38% of animal sheds had provision of pucca drainage facility of urine. Sixty percent of the respondents adopted some kind of measures to protect the animals from extreme weather conditions. Most of respondents (92.67%) practiced regular vaccination to their animals against Foot and Mouth disease and Haemorrhagic Septicaemia disease. About 40% of the respondents practiced deworming of their dairy animals regularly and 43.33% of respondents followed various practices for control of ecto–parasites. Majority (64%) of respondents had cleaned animal sheds and 58.67% of respondents got treatment to their sick dairy animals by veterinarian.